A green transition orchestrated from Big Tech clouds? - Rikap, Cecilia; Weko, Silvia (Globalizations, 2025)
As the European Commission and other actors are advocating for a ‘twin transition’ where digitalization enables sustainability, we look at the political and business strategies of Big Tech concerning artificial intelligence (AI) and the cloud for addressing ecological problems. Our paper explores how Google and Amazon are positioning themselves to steer and even control an ecological transition fit for their purposes. We find that their strategy relies on combining dressed up narratives with products (including digital services) that promote individual actions while Big Tech companies exclusively retain knowledge that provides a systemic view of the planet. Their AI and cloud services for the green transition lock in states and firms expanding Google and Amazon's profits and their spheres of control. This not only expands Big Tech's intellectual rents but also changes the trajectory of the ecological transition to one that benefits them while hampering other alternative -more just- pathways.
CRIS-Team Scopus Importer:2025-09-26
Keywords: artificial intelligence; Big Tech; ecological crisis; techno-solutionism; Twin transition